A Millimeter-Wave Single-Bit Reconfigurable Intelligent Surface With High-Resolution Beam-Steering and Suppressed Quantization Lobe - Aditya S. Shekhawat; Bharath G. Kashyap; Russell W. Raldiris Torres; Feiyu Shan; Georgios C. Trichopoulos (IEEE Open Journal of Antennas and Propagation)
We present a 1-bit reconfigurable intelligent surface (RIS) operating at millimeter-wave frequencies that suppresses the undesired grating lobes encountered in binary phase modulation schemes and achieves high resolution beam steering. We incorporate fixed, random phase delays at each unit cell of the surface which breaks the periodicity of the phase quantization error and suppresses side lobes. Additionally, the random phase delays reduce the beam pointing error – a limitation of binary RISs - which can be beneficial in applications that require high resolution beam steering. The proposed topology allows for scalable RIS apertures that are compatible with printed circuit board (PCB) fabrication technology. It consists of four metasurface tiles of 256 radiating elements ( $16× 16$ ) connected on a separate control board that houses the control unit and power supply. The prototype is designed to operate at 27.2 GHz and perform electronic beam steering in ±60° in both azimuth and elevations planes. A quantization lobe reduction of more than 10 dB is achieved with the proposed technique and the surface is well suited for mmWave 5G communication scenarios to enhance signal coverage and signal-to-noise ratio.